Significance of Gastric Wall Thickening Detected in Abdominal CT Scan to Predict Gastric Malignancy. (20th November 2019) - Akbas, A.; Bakir, H.; Dasiran, M. F.; Dagmura, H.; Ozmen, Z.; Yildiz Celtek, N.; Daldal, E.; Demir, O.; Kefeli, A.; Okan, I.
Abstract : Background . Early diagnosis of gastric cancer is one of the most important parameters affecting the survival of the disease. In this study, we aimed to stress the importance of antrum wall thickness in CT examination. Method . The study included 111 patients between ages of 18 and 95 who had antral wall thickening in computed tomography and also had endoscopic evaluation performed in the same clinic. The patients were divided into two groups as benign and malignant according to the pathology results. The thickness of the antrum wall in computed tomography, hemoglobin and albumin levels, and age was compared among these two groups. Parameters with significant differences were further analyzed by multivariate analysis using logistic regression analysis. Results . Of the 111 patients included in the study, 57 were male and 54 were female. Mean age was 65 years. Fifty-one patients were classified as benign and 60 patients as malignant. Mean age of the malignant patients was 70, while that of benign patients was 59 (p < 0.05 ). Antrum wall thickness was 13.68 ± 3.27 mm in malignant patients and 9.22 ± 2.17 mm in benign patients (p < 0.05 ). Similarly, hemoglobin level was significantly different in malignant and benign patients (10.78 ± 1.57 g/dl and 12.64 ± 1.43 g/dl, respectively; p < 0.05 ). Albumin levels were 3.36 ± 0.57 mg/dl in malignant patients and 3.97 ± 0.57 mg/dl in benign patients (p < 0.05 ). Conclusion . Evaluation of antrum wall thickness, age, hemoglobin, and albumin values together may contribute to distinguishing the benign and malignant pathologies involving this region in patients with suspected stomach wall thickening in abdominal CT scan.